Immune Responses to a Live Virus Vaccine Candidate and Protection against Pseudorabies Virus Infection - Saeed Ali Bablker, Abdel-Wahid (1999)

(untitled)
A comparative study of three Malaysian pseudorabies virus (PrV) isolates, one Malaysian PrV strain and one American reference PrV was carried out using restriction endonucleases. Variations were observed among these viruses when their DNAs were digested with only Kpn I and BamH I enzymes. The Malaysian strain (PrV-mA1p) showed restriction pattern which was different from its parental virus. An obvious differences were observed between the reference virus and the Malaysian PrVs. When the SDS-PAGE technique was employed, no significant variations in protein profiles of the PrVs but variations in their immunogenic proteins were observed when they were reacted against homologous and heterologous antisera in Western blotting. The viruses were suggested to belong to the same serologic sub-type using SNT and ELISA tests. Experiments in mice demonstrated that all the viruses were pathogenic to various extents while PrV-mAlp was found to be non-pathogenic even when mice were infected with 108 p.f.u. The study showed that 100% protection was obtained following immunization of mice with at least 105 p.f.u. However, the protection level was highly dose and route of immunization dependent. Antibody (Ab) responses to PrV-mAlp were correlated with the protection levels obtained and demonstrated to persist in mouse serum for five consecutive months. Low levels of neutralizing Ab (N-Ab) were detected in mice following immunization with PrV-mAlp depending on the dose and route of inoculation. They were correlated with the protection levels but not with the ELISA Ab titres. Higher DTH responses were observed in mice immunized with PrV-mAlp especially via intranasal route (i.n.). A second dose of immunization slightly increased the DTH response. A significant (p<0.05) increase of PrV-mAlp growth was observed in mice tissues treated with immunosuppressive agents. However, the highest virus titres were detected in cyclophosphamide (CPS)treated mice followed by dexamethasone (DXM)- and flumethasone (FLM)treated mice. A significant (p<0.0l) decline in Ab titres following treatment of mice with all the drugs was noted. However, the highest decline was observed in CPS-treated mice. PrV-mA1p was reactivated in low titres from latently infected nervous tissues of mice using CPS and DXM but not from respiratory tissues. Increases in the protection levels and Ab responses were observed in mice immunized with the algammulin-adjuvanated PrV-mAlp. PrV-mAlp was also found to be non-pathogenic for swine following inoculation of piglets with up to 108 p.f.u. but displayed high levels of immunogenicity in piglets, hence the virus was highly suitable to be proposed as a live virus vaccine against PrV infection.